Rola osłon w rachunkowości - Rówińska, Małgorzata (The Essence of Hedges, 2005)
A key element in most hedges is a "matching" process. Something exposed, for example, to price volatility is offset against such volatility going the other way. Hedges can be accomplished either by the use of various financial instruments, especially derivatives. Hedges are seldom able to fully eliminate risk, [t may not be possible to find a financial instrument which exactly fits the risk of the item being hedged. The recognition, measurement and disclosure of hedging activities define the accounting standards. The accounting for the hedged item needs to be matched to the accounting for hedging financial instrument.(original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1085, s. 325-329